Observation and Theory in Science - Nagel, Ernest Sylvain (Johns Hopkins University Press, 2019)
Originally published in 1971. The three contributions collected in this volume deal with different aspects of a single theme-the logical status of scientific theories in their relation to observation. These lectures, authored by different thinkers, treat this theme in connection with some controversies in the philosophy of science. A nonspecialist who reads these lectures should realize that the theme itself is a perennial one with an ancient lineage. It has concerned philosophers from the earliest era of philosophy on down through the centuries. A central philosophical issue at stake in the lectures is the question of whether scientific theories are testable in terms of our observations such that we can know whether some theories are true and others false. Although differing in their emphases, all three contributors seek a more plausible and nonskeptical philosophical account of the status of scientific theories in relation to observation.